An alternative axiomatic characterisation of pricing operators. (9th December 2016) - Kassberger, Stefan; Liebmann, Thomas
Abstract: In the spirit of the axiomatic approach by Rogers (1998) we show the equivalence between a set of assumptions on the behaviour of prices and the existence of a representation of these prices as conditional expectations. We rely on only weak assumptions and avoid any a priori modelling of negligible events or of any market filtration. Rather, both endogenously emerge along with the representation as conditional expectations.